Stability and reactivity of copper oxo-clusters in ZSM-5 zeolite for selective methane oxidation to methanol - Li, Guanna; Vassilev, Peter; Sanchez-Sanchez, Maricruz; Lercher, Johannes A.; Hensen, Emiel J.M.; Pidko, Evgeny A. (Journal of catalysis, 2016)
[Display omitted] •Cu speciation in ZSM-5 zeolite depends on the conditions of thermochemical activation.•Trinuclear [Cu3O3]2+ cationic clusters are preferentially formed in HZSM-5 upon calcination.•Trinuclear Cu-oxo clusters favor the direct methane to methanol oxidation.•Methane activation by binuclear [Cu2O]2+ results in strongly bound surface intermediates. A periodic density functional theory study complemented by ab initio thermodynamic analysis was carried out to identify the active sites and mechanism of selective oxidation of methane to methanol in Cu/ZSM-5 catalysts. We systematically analyzed structure and stability of a wide range of potential extra-framework Cu complexes in ZSM-5 to address Cu speciation in realistic zeolite materials. We demonstrate that depending on the conditions of catalyst activation, binuclear [Cu(μ-O)Cu]2+ species and trinuclear oxygenated [Cu3(μ-O)3]2+ clusters can preferentially be stabilized in ZSM-5. The trinuclear Cu sites are the most stable extra-framework Cu species in Cu/ZSM-5 activated by calcination, whereas the formation of the binuclear complexes is favored under O2-poor atmosphere. Although both types of Cu complexes contain extra-framework O−, radical species necessary for the homolytic C–H bond cleavage, the reaction paths for methane conversion that they provide are drastically different. Binuclear Cu sites react with CH4 stoichiometrically to yield methoxy groups strongly bound in the zeolite micropores. In contrast, the trinuclear [Cu3(μ-O)3]2+ cluster favors the direct conversion of CH4 to CH3OH coordinated with the partially reduced Cu complex. These computational findings point to the trinuclear Cu-oxo clusters in ZSM-5 as the potential candidates for promotion of the low temperature direct conversion of CH4 to CH3OH.